The Clinical Spectrum of De Novo Donor‐Specific Antibodies in Pediatric Renal Transplant Recipients. Issue 10 (28th August 2014) - Kim, J. J.; Balasubramanian, R.; Michaelides, G.; Wittenhagen, P.; Sebire, N. J.; Mamode, N.; Shaw, O.; Vaughan, R.; Marks, S. D.
<x xml:space="preserve">Abstract</x> The development of donor‐specific HLA antibodies (DSA) is associated with worse renal allograft survival in adult patients. This study assessed the natural history of de novo DSA, and its impact on renal function in pediatric renal transplant recipients (RTR). HLA antibodies were measured prospectively using single‐antigen‐bead assays at 1, 3, 6 and 12 months posttransplant followed by 12‐monthly intervals and during episodes of allograft dysfunction. Of 215 patients with HLA antibody monitoring, 75 (35%) developed DSA at median of 0.25 years posttransplant with a high prevalence of Class II (70%) and HLA‐DQ (45%) DSA. DSA resolved in 35 (47%) patients and was associated with earlier detection (median, inter‐quartile range 0.14, 0.09–0.33 vs. 0.84, 0.15–2.37 years) and lower mean fluorescence intensity (MFI) (2658, 1573–3819 vs. 7820, 5166–11 990). Overall, DSA positive patients had more rapid GFR decline with a 50% reduction in GFR at mean 5.3 (CI: 4.7–5.8) years versus 6.1 (5.7–6.4) years in DSA negative patients (p = 0.02). GFR decreased by a magnitude of 1 mL/min/1.73 m2 per log10 increase in Class II DSA MFI (p < 0.01). Using Cox regression, independent factors predicting poorer renal allograft outcome were older age at transplant (hazard ratio 1.1, CI: 1.0–1.2 per year), tubulitis (1.5, 1.3–1.8) and microvasculature injury (2.9, 1.4–5.7). In conclusion, pediatric RTR with de novo DSA and microvasculature injury were at risk of allograft failure.